Structure of wall layers in Selaginella kraussiana microspores (Lycophyta) - Morbelli, Marta Alicia (2010)
A similarity was found in both construction and ultrastructure between the two exospore layers in microspores of Selaginella kraussiana. The exospore is made up of two different kinds of rods. One of the kinds of rods are large, 100–150 nm in width, while the other are tubular rods 10–15 nm in diameter. The large rods are wider at the base of the spines than in the upper part, possibly due to flattening or compression. Both the outer and the inner exospores have a stranded surface that is very pronounced in the microspores of this species. Fibrous strands persisting the scanning electron microscope and transmission electron microscope (TEM) fixations were observed on the spore surface proximally and through perforations (exospore channel openings). This net of fibres penetrates and fills the space of the cavities within large channels through the outer and inner exospore and within the gap. According to our interpretation, these strands would be produced by the tapetum and are probably related to the nourishment of the developing microspores. Contrast varies in TEM sections after cytochemical stains, but this appears to be due to transitory substances, e.g. carbohydrates, rather than to be a substantial difference in basic composition between inner and outer exospore layers.